2022
DOI: 10.1186/s13756-022-01163-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality and antimicrobial efficacy of locally manufactured alcohol-based hand sanitizers marketed in Addis Ababa, Ethiopia in the era of COVID-19

Abstract: Background The coronavirus disease 2019 (COVID-19) has been rapidly spreading across the globe since the World Health Organization (WHO) has declared the disease outbreak as a global pandemic on March 11, 2020. Hand hygiene, via either regular handwashing with soap and water or using hand sanitizers, is among the various measures that need to be followed to control the outbreak of the disease. Alcohol-based hand sanitizers (ABHS) are the “gold standard” for hand disinfection because of their br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…A similar study was performed in Ethiopia recently to analyze the quality and efficacy of local brands of hand sanitizers. The results of this study revealed that over one-third of the analyzed hand sanitizers failed to comply with the guidelines of WHO with respect to the limit of ethanol and hydrogen peroxide in the formulation [48]. Similar results were also obtained in a study conducted on marketed hand sanitizers in Kenya.…”
Section: Challenges In Effective Sanitation Due To Covid-19supporting
confidence: 78%
“…A similar study was performed in Ethiopia recently to analyze the quality and efficacy of local brands of hand sanitizers. The results of this study revealed that over one-third of the analyzed hand sanitizers failed to comply with the guidelines of WHO with respect to the limit of ethanol and hydrogen peroxide in the formulation [48]. Similar results were also obtained in a study conducted on marketed hand sanitizers in Kenya.…”
Section: Challenges In Effective Sanitation Due To Covid-19supporting
confidence: 78%
“…It should be noted that it was beyond the scope of the current study to carry out sophisticated experimentation in order to further evaluate to which extent the antibacterial properties of these disinfectants are attributed to the inclusion of the essential oils. It has been shown earlier that ethanol, as a chemical substance, is capable of inactivating Staphylococcus aureus and Pseudomonas aeruginosa when used as such or as a substance in alcohol-based hand sanitizers [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…However, the level of acidity isn't high enough to cause severe skin irritation, making these products acceptable to the general public. The near neutrality of these hand sanitizers is imperative to the efficacy and acceptability in the market (Selam et al, 2022).…”
Section: Physical Proper Es Of Hand Sani Zersmentioning
confidence: 99%
“…Because the effectiveness of alcohol-based hand sanitizers depends on the ethanol or isopropanol content, the CDC recommends the use of alcohol-based hand sanitizers greater than 60% ethanol or 70% isopropanol as the preferred form of hand hygiene, whereas the WHO recommends the strength of 80% ethanol or 75% isopropanol as standard for hand hygiene care. However, the quality and safety of commercially available hand sanitizers is a major concern for the regulatory authorities because many studies reported that the ethanol content of hand sanitizers in tested samples varies both within and between countries (Selam, 2020;Selam et al, 2022).…”
Section: Introductionmentioning
confidence: 99%